2010
DOI: 10.1002/ccd.22505
|View full text |Cite
|
Sign up to set email alerts
|

Stent graft exclusion of a pseudoaneurysm in a Blalock‐Taussig shunt

Abstract: This case is the first report of slow-growing pseudoaneurysm after vessel dissection secondary to two stents implantation into classic Blalock Taussig shunt in a patient with pulmonary atresia and ventricular septal defect. Pseudoaneurysm was successfully excluded by a percutaneous approach with self-expandable stent graft deployment from the aorta to the middle of the Blalock Taussig shunt. Nearly 3 years after the procedure, the classic BT is patent, and there were no restenosis or thrombosis in spite of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, corrective surgery was not possible in most patients because of pulmonary artery hypoplasia and anatomic issues. Recently, percutaneous techniques including transcatheter thrombolysis, mechanical thrombectomy, balloon angioplasty, and stent insertion have become attractive alternatives to surgery with interesting advantages ( 18 , 50 , 51 ). When compared to surgery, catheter interventions offer decreased bleeding risk, post-interventional wound pain, and infection, as well as shorter hospital stay ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, corrective surgery was not possible in most patients because of pulmonary artery hypoplasia and anatomic issues. Recently, percutaneous techniques including transcatheter thrombolysis, mechanical thrombectomy, balloon angioplasty, and stent insertion have become attractive alternatives to surgery with interesting advantages ( 18 , 50 , 51 ). When compared to surgery, catheter interventions offer decreased bleeding risk, post-interventional wound pain, and infection, as well as shorter hospital stay ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Successful placement of covered coronary stents, after coil embolization was described in several cases with complicated large pseudoaneurysm formations ( 86 ). In addition, it has been reported that slow-growing pseudoaneurysm after BTS stent implantation was successfully excluded with a self-expandable stent graft without complication in the immediate and short-term follow-up ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoaneurysms can be treated using either the surgical or the transcatheter approach. 2 The transcatheter approach is preferred in patients who are critically ill or having active hemorrhage. Both of our patients had massive hemoptysis; therefore, an operation with or without cardiopulmonary bypass may have been more risky for them.…”
Section: Discussionmentioning
confidence: 99%
“…The primary complications of shunt-related pseudoaneurysm include rupture and massive pulmonary hemorrhage. [1][2][3][4] We describe two children herein who had recurrent pulmonary hemorrhage secondary to pseudoaneurysms of the left subclavian artery following modified Blalock-Taussig shunt procedures.…”
Section: Introductionmentioning
confidence: 99%